Keys of educational change in Ecuador - Agustín De la Herrán Gascón; Ana Isabel Ruiz Cedeño; Fernando Lara Lara (FahrenHouse, 2018)
The article analyzes the educational system in Ecuador. The Ecuadorian education system arouses international interest, especially in Latin America. In this essay we will try to answer these questions: What might be the relevant keys from the public education in Ecuador? Why has it reached its present level of development, particularly in inclusive education? What fundaments and policies are behind the results of the goals from Education for All (EFA) 2000-2015 From the Dakar framework for Action? (World Education Forum, 2000). In light of these issues, the goal is to understand key factors and reasons that have contributed to the development of the Ecuadorian public education. In terms of methodology, the approach is qualitative, dialectical, documentary and descriptive (Mc Millan and Schumacher, 2005). The research is proposed as a case study, where the choice of the case is justified by its novelty, its degree of development and its emphasis on inclusion and equity in all educational levels. With this aim, it is made a descriptive analysis of the rules underlying the changes in the educational system in Ecuador in the last three decades and it is carried out, particularly since 2008, following the last Constitution (Constituent Assembly, 2008). Tables as an analytical contribution of the authors are offered. Also data endorsed by authors and agencies of maximum national and international prestige are detailed and they realize the effectiveness of policies and such changes.